Entangled Narratives. Encountering Political Subjectivities of People with Albinism in Tanzania - Giorgio Brocco (AM. Rivista della Società Italiana di Antropologia Medica, 2020)
Entangled Narratives. Encountering Political Subjectivities of People with Albinism in Tanzania. After the spread of media news about the attacks against people with albinism in Tanzania, humanitarian activism and media debates have accelerated the emergence and production of discourses about people with the condition in the country. Victimhood, deservingness and equivalence of albinism with disability represent three of the most recurring media and humanitarian narratives. Based on data collected over 19 months of fieldwork in Tanzania, the present article explores how discourses and ideas about albinism have circulated among and been reformulated by people with albinism to deconstruct shared conceptions of normalcy and affirm their agency in the Tanzanian public arena. The ethnographic material shows in which multiple ways the intertwinement of global actions and everyday practices related to albinism have strengthened already-existing political subjectivities, (re)shaped political claims, and articulated ideas of (dis)belonging.Narrazioni complesse. Incontro con le soggettività politiche delle persone con albinismo in Tanzania Dopo la diffusione di notizie da parte dei media sugli attacchi contro le persone con albinismo in Tanzania, l’attivismo umanitario e i dibattiti mediatici hanno accelerato l’emergere e la produzione di discorsi riguardanti le persone con la condizione. Vittimismo, merito e l’equivalenza tra l’albinismo e disabilità costituiscono tre delle più ricorrenti narrazioni mediatiche e umanitarie. Attraverso i dati raccolti durante 19 mesi di ricerca sul campo, l’articolo esplora come discorsi e idee sull’albinismo sono circolate e sono state riformulate per decostruire concezioni condivise dell’idea di “normalità” e affermare la loro agentività nell’arena pubblica in Tanzania. Il materiale etnografico qui analizzato mostra in quali multipli modi l’intreccio di azioni globali con pratiche odierne in relazione all’avere l’albinismo hanno rafforzato soggettività politiche già esistenti, riformulato richieste politiche e articolato varie idee di appartenenza e disappartenenza